THE INFLUENCE OF BRAND IMAGE AND PRODUCT QUALITY ON THE PURCHASE DECISION OF ACER BRAND LAPTOP (Case Study of STIE BINA KARYA Tebing Tinggi Students) - CAHYADI, LUKIETO (International Conference on Health Science, Green Economics, Educational Review and Technology, 2020)
This study aims to determine "The Influence of Brand Image and Product Quality on Purchase Decisions of Acer Brand Laptops (Case Study of STIE BINA KARYA TEBING TINGGI STUDENTS)". The sampling method used in this study was to use the Saturated Sampling formula for 39 samples who were Acer laptop users at STIE BINA KARYA students. Based on the results of the analysis of hypothesis 1, it can be concluded that the first hypothesis is accepted, meaning that the Brand Image variable (X1) influences the Purchase Decision variable (Y) with a tcount (3.359) > ttable (2.434) . Based on the results of the analysis of hypothesis 2, it can be concluded that the second hypothesis is rejected, meaning that the Product Quality variable (X2) has no effect on the Purchase Decision variable (Y) with a tcount (0.387) < ttable (2.026). 3.